Setting TOU electricity tariffs for NTU electricity consumers - Goh, Michael Yeow Liang (2014)
With rising electricity costs and advanced technology advancements, it has stimulated considerable research in the area of residential consumers’ electricity usage. Two important focuses in the area of consumer response are electricity consumption costs and price based programs that determine the prices for the electricity in accordance to the time-of-use (TOU). Power generation companies all over the world are able to make use of advanced metering infrastructure to tackle these two focuses. Advanced metering infrastructure consists of smart meters which allow residential consumers to check real time electricity consumption which can implement different kind of tariff schemes other than the flat rate tariff scheme One of the price based programs is the time-of-use (TOU) rate tariff scheme. The two-tier TOU rate tariff scheme consists of two prices which are the TOU peak and non-peak rates. Under this scheme, residential consumers are charged based on peak and non-peak electricity rates during the respective peak and non-peak periods of the month. Currently, NTU buys electricity from Senoko Energy in their distribution of electricity to household users, building users and tenants, canteen operators and respective consumers. Traditionally, residential consumers pay flat rate tariff throughout the 24-hour period in a day. To see if this TOU rate tariff scheme is feasible for adoption in NTU, a demand response management analysis consisting of a two tier TOU algorithm for existing smart meters’ data is conducted for this purpose.